Energetic, entropic and economic analysis of a heat pump coupled humidification dehumidification desalination system using a packed bed dehumidifier. (15th August 2019) - He, W.F.; Wen, T.; Han, D.; Luo, L.T.; Li, R.Y.; Zhong, W.C.
Highlights: A MVCHP coupled HD desalination system with packed bed dehumidifier is proposed. Energetic and entropic analysis is achieved with the modified effectiveness during humidification. The top water production and GOR of the HD desalination system reach 71.56 kg h −1 and 5.28. The cost of the produced water is obtained as 0.018 $ L −1 with a lifetime of 10 years. Advantages of energy conservation for the HD desalination system are proved. Abstract: In this paper, the humidification dehumidification (HD) desalination system, driven by a mechanical vapor compression heat pump (MVCHP), is proposed. The direct contact dehumidifier, with packings filled, is applied to condense the humid air for water producing. On the basis of the thermodynamic laws, the energetic and entropic analysis, with the modified effectiveness to describe the heat and mass transfer characteristics of humidification, are first achieved to assess the desalination performance of the combined system. The influence laws from the terminal temperature difference (TTD) of the evaporator, the pressure ratio (PR) during compression and pinch temperature difference (PTD) of the condenser on the desalination performance are also explored and presented. The research results presented that the top thermodynamic performance of the MVCHP coupled HD desalination system arises as 71.56 kg h −1 for the water production, 5.28 for the gained-output-ratio (GOR) and 1.73 kJ kg −1  K −1 for the specific entropy generation rate, while two fully coupled cases at 1.21 and 1.96 for the mass flow rate ratio will emerge. It is found that water production can be elevated effectively through increasing the pressure ratio, while the peak value of GOR keeps at the design conditions. Furthermore, the positive effects from lower values both for the TTDe and PTDcon on the performance of the MVCHP coupled HD desalination system are proved. After the economic analysis, it is calculated that the cost of fresh water is about 0.018 $ L −1 with a lifetime of 10 years. According to the performance comparison, the great potential of energy conservation for the MVCHP coupled HD desalination system are validated, although the water production will be reduced after the integration of the MVCHP.